Effectiveness of a process-based executive function intervention on arithmetic knowledge of children with Developmental Dyscalculia. (August 2022) - Nazari, Somayeh; Hakiminejad, Farnaz; Hassanzadeh, Saeid
Abstract: Background: Arithmetic knowledge has long been known as an essential factor for educational and vocational success. Aims: This study aims to explore the effectiveness of a process-based Executive Function (EF) intervention program on the improvement of components of arithmetic. Methods and procedure: A goal-directed sampling method was applied in this study. Participants were assigned into active control and experimental groups. Semi-experimental design with pre-test, post-test and follow-up was utilized in this research. Participants were included in this study based on their WISC-IV and Key-Math test performance. 30 male students aged 8–10 years with a formal diagnosis of Developmental Dyscalculia (DD), selected from a learning disability center in Ahvaz, Iran, participated in the study. The pre-test took 1 month, the intervention including 17 sessions, took two months and the post-test took 1 month. All the students' arithmetic knowledge were tested in pre-test, post-test, and 3 months after post-test to test the longevity of the intervention effects. Repeated measure Univariate Analysis of Variance was conducted in this study. Outcomes and results: The results indicate that the students who attended the intervention, outperformed control group in the components of factual and procedural arithmetic in post-test and follow-up, however; the performance of two groups in conceptual knowledge was not different. This study contributes to the emerging evidence that EF intervention may improve factual and procedural arithmetic knowledge in children with DD. Conclusions and implications: Process-based EF interventions can improve arithmetic knowledge of students with DD, which can contribute to the literature of this area What this paper adds?: The current research helps cognitive science to present a more meticulous theoretical and conceptual pattern for EF components and math, using process-based EF intervention programs with arithmetic content. Furthermore, this research allows for specification of cognitive fundamentals of arithmetic development and understanding the mechanisms underlying the transfer effect of EF intervention to math. The findings of this research can contribute to evidence-based EF intervention studies and help educational psychologists in preparation of appropriate curricula based on the fundamental components of arithmetic development in preschool and primary school. Highlights: Process-based executive function intervention improves procedural arithmetic knowledge in developmental dyscalculia. Process-based EF intervention improves procedural arithmetic knowledge of children with DD. Process-based executive function intervention yields far-transfer to arithmetic knowledge.